2022
DOI: 10.1021/jacs.2c10584
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Amplification through the Interplay of Racemizing Conditions and Asymmetric Crystal Growth

Abstract: Amplification of enantiomeric excesses (ee) is routinely observed during chiral crystallization of conglomerate crystals for which the enantiomers undergo racemization in solution. Although routes comprising a combination of crystal growth and dissolution are frequently used to obtain enantiopure molecules, crystal growth by itself has rather been considered as a source of enantiomeric erosion and discounted as a potential source of enantiomeric amplification. Counterintuitively, we here demonstrate striking e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Specifically, we recently showed that slow growth and deep cooling result in large asymmetric crystallization with virtually exclusive growth of the majority phase. 16 In contrast, we here realize that fast heating should be favourable to keep the overall cycle time short. Hence, we hypothesize that a process combining slow crystal growth and fast dissolution would be ideal to achieve rapid deracemization.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Specifically, we recently showed that slow growth and deep cooling result in large asymmetric crystallization with virtually exclusive growth of the majority phase. 16 In contrast, we here realize that fast heating should be favourable to keep the overall cycle time short. Hence, we hypothesize that a process combining slow crystal growth and fast dissolution would be ideal to achieve rapid deracemization.…”
mentioning
confidence: 85%
“…Finally, the supersaturation increases rapidly at high temperatures, leading to undesired primary nucleation and fast growth with low chiral enrichment by asymmetric crystal growth. 16 These considerations highlight the importance of solvent choice for solvent cycling-induced deracemization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] However, systems deviating from this conventional mechanism have questioned the comprehensiveness of this framework, sparking vigorous experimental and theoretical investigations into nonclassical crystallization (NCC). [3][4][5][6] The primary objective of NCC studies is to understand and regulate growth processes driven by particle attachment, encompassing nanoparticles, clusters, and liquid precursor phase droplets. [7][8][9] Achieving even partial success in these pursuits holds not only the potential for a more profound understanding of diverse geochemical and biomineralization processes but also for the development of advanced synthesis techniques for materials unconstrained by the geometric limitations of crystal unit cells.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of these solids from a homogeneous phase typically relies on the stochastic and dynamic addition of atoms, ions, or molecules [1,2] . However, systems deviating from this conventional mechanism have questioned the comprehensiveness of this framework, sparking vigorous experimental and theoretical investigations into nonclassical crystallization (NCC) [3–6] . The primary objective of NCC studies is to understand and regulate growth processes driven by particle attachment, encompassing nanoparticles, clusters, and liquid precursor phase droplets [7–9] .…”
Section: Introductionmentioning
confidence: 99%